The Evaluation of Children Admitted to Ege University Faculty of Medicine After an Earthquake in Terms of Health Services - Merve Tosyalı; Feyza Koç (Galenos Yayinevi, 2023)
Aim: The most vulnerable victims of natural disasters are children. Health professionals have made great efforts to improve the health and psychosocial conditions of children from this region after the major earthquake disaster we experienced. This study aimed to evaluate those earthquake victims referred to our department of pediatrics in terms of health services and to share the results. Materials and Methods: Children who were transferred to Ege University Faculty of Medicine, Department of Pediatrics after the earthquake were included in this study. It was recorded from which province these children came from, their age, gender, whether they were crushed or not, their physical health status, the duration of their stay in the hospital, their vaccination status, and whether there was any loss of parent or sibling. Results: Five earthquake victims were referred, three from Hatay, one from Malatya, and one from Iskenderun. Of these children aged between 16 months and 16 years, 4 were boys, and 1 was a girl. In two of our patients, both lower extremities were amputated due to being trapped under rubble. The tetanus vaccine was administered to all children. It was discovered that 4 of our five patients hospitalized had lost a parent and/or sibling. The mean duration of stay in the hospital was 10.2 days. Conclusion: It is crucial to determine earthquake survivors' needs during treatment, to work as multidisciplinary teams, and to make a follow-up plan for after discharge.